The Effectiveness of BBC Learning English to Teaching Reading for Eleventh Grade Students - Paramita, Aprilian; Ayu, Mutiara (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The significance of English language acquisition within the Indonesian education system lies in its impact on students' futures, but they face many challenges in mastering it. It discusses the fundamental skills required for proficiency, including reading, listening, speaking, and writing, emphasising enhancing listening abilities. The framework integrates English into education, and language centres collaborate with other departments. Furthermore, it emphasises the importance of reading comprehension and the role of resources like BBC Learning English in improving this skill. A study was conducted at SMAN 14 Bandar Lampung, aiming to evaluate eleventh-grade students' reading proficiency and the impact of BBC Learning English on their language abilities. Additionally, it outlines the research methodology, which employs quantitative analysis with a one-group design to assess students' reading comprehension levels and the effectiveness of the intervention. The researcher used a pre-test and post-test to measure the students' capacity to read narrative text. The research found improved scores between the pre-test and post-test. The mean of the pre-test was 60.89 while the post-test was 78.54; the difference was 17.65 in the mean. The hypothesis table shows that the significance (2-tailed) value is 0.00, which is below the threshold of 0.05. Therefore, we reject the null hypothesis (H0) and accept the alternative hypothesis (H1), confirming the existence of a statistically significant difference between the pre-test and post-test scores.